Exploring environmental adaptation mechanisms of symbiotic microorganisms in marine reducing ecosystems: harnessing genomic comparison to unveil the underlying mechanisms - Peng Zhou; Peng Zhou; Xue-Qing He; Xue-Qing He; Peng Xu; Peng Xu; Dong-Sheng Zhang; Dong-Sheng Zhang; Dong-Sheng Zhang; Chun-Sheng Wang; Chun-Sheng Wang; Chun-Sheng Wang (Frontiers in Marine Science, 2025)
Various invertebrates, with microorganisms as their symbionts, inhabit diverse and dynamically changing environments such as hydrothermal vents (HVs) and cold seeps (CSs). The ongoing \dispersal of these symbionts is crucial for their biogeographic distribution and connectivity, which in turn facilitates the persistence of mutualistic relationships. To gain insights into the mechanisms underlying the adaptation of symbionts in response to environmental changes, this perspective analyzed two genes related to sulfur metabolism in the symbionts, based on their genome annotations. Our findings revealed that the gene encoding cysteine desulfurase (CSD) is ubiquitous among these symbionts, regardless of their geographic locations, hosts, or genome sizes. This suggests that these symbionts possess the ability to utilize sulfur from cysteine. Similarly, genes encoding sulfate adenylyltransferase (SAT), which is essential for sulfate assimilation, are also widely present in the genomes of the symbionts, with notable exceptions being some isolates from sponges. Notably, most of the investigated symbionts possess both sat and csd genes, hinting at their capability to utilize both organic and inorganic sulfur resources. The presence of both sat and csd genes may confer an advantage to the symbionts while cessation of hydrothermal and cold seep activity or during their dispersal among isolated locales. Further comparative genomic studies, particularly those focusing on the versatile adaptation strategies of symbionts across different life stages, can enhance our understanding of their ecological fitness and broaden our knowledge about how these symbiotic microorganisms successfully dwell in the dynamic marine environments.